A study on wavelet analysis of SSVEP Signals - Babu, Bincy; Chandrasekaran, R; Elsa Joseph, Josline; Shalem Rahul, Thella; R Thamizhvani, T; Josephin Arockia Dhivya, A (International Journal of Engineering and Technology, 2018)
Almost every Brain Control Interfcae (BCI) system is framed based on Steady State Visual Evoked Potential (SSVEP) which is predicted through distinguishing overriding frequency components in Electroencephalography (EEG) signals. The proposed system aims in accurate feature extraction of SSVEP signals. Power spectral analysis and wavelet analysis are done for feature analysis. The feature set variation for male and female subjects are obtained. Compared power spectral estimation and wavelet analysis, merits and demerits of each approach can be identified from the outcomes. It offers a theoretical reference of practical choice for BCI application.Â Â